Correction: The highly efficient removal of HCN over Cu8Mn2/CeO2 catalytic material. Issue 27 (11th May 2021) - Yi, Zhihao; Sun, Jie; Li, Jigang; Yang, Yulin; Zhou, Tian; Wei, Shouping; Zhu, Anna
Abstract : Correction for 'The highly efficient removal of HCN over Cu8 Mn2 /CeO2 catalytic material' by Zhihao Yi et al., RSC Adv., 2021, 11, 8886–8896. DOI: ; 10.1039/D0RA10177J